Clinical Outcomes of Leadless Pacemaker - a Systematic Review - Sílvia Maria Ferreira de Oliveira (2020)
INTRODUCTION: Transvenous pacemakers are associated with a significant amount of complications. Leadless pacemakers (LP) are emerging as an alternative to conventional devices. This article provides a systematic review of patient eligibility, safety and clinical outcomes of the LP devices. EVIDENCE ACQUISITION: A systematic search for articles describing the use of LP was conducted. Out of two databases, 24 articles were included in the qualitative analysis. These articles comprised a total of 4739 patients, with follow up times of 1-38 months. Further information was obtained from 10 more studies. EVIDENCE SYNTHESIS: From a population of 4739 patients included in the qualitative analysis, 4670 LP were implanted with success (98.5%). A total of 248 complications were described (5.23%) during the follow-up. The most common were pacing issues such as elevated thresholds, dislodgements or battery failure (68), events at the femoral access site such as hemorrhage, hematoma or pseudoaneurysms (64) and procedure related cardiac injuries such as cardiac perforation, tamponade or pericardial effusion (47). There were 360 deaths during the follow-up and 12 were described as procedure or device related. Four studies presented the strategy of using a combined approach of atrioventricular node ablation (AVNA) and LP implantation. CONCLUSIONS: Leadless pacemakers seem to have a relatively low complication rate. These devices may be a good option in patients with an indication for single-chamber pacing, in patients with conditions precluding conventional transvenous pacemaker implantations. Studies directly comparing LP and transvenous pacemakers and data on longer follow-up periods are needed.